USE OF TUMOR NECROSIS FACTOR-A INHIBITORS IN RHEUMATOID ARTHRITIS: TOPICAL ASPECTS - E L Luchikhina; D E Karateev; Ye L Luchikhina; D E Karateyev (Современная ревматология, 2008)
The use of tumor necrosis factor (TNF) а inhibitors in combination with methotrexate remains the basic method for treating active rheumatoid arthritis (RA). This line in antirheumatic therapy is rapidly developing. A number of unsolved issues associated with the selection of patients (particularly at the early stage of RA) to be treated with TNF а antagonists, the prediction of its efficiency, the study of comparative aspects of therapy are on the agenda. The Russia's emergence of the latest TNF а inhibitor adalimumab that has unquestioned merits opens new vistas for the treatment of RA.